The Ash Wednesday supper - Bruno, Giordano 1548-1600 (University of Toronto Press, 2018)
"Giordano Bruno wrote this dialogue in 1583. The Ash Wednesday Supper is concerned with two major themes: a cosmological theme concerning the new post Copernican astronomy and Bruno's infinitist reading of it; and the other a social/historical theme concerning the english society, both high and low, of which Bruno was a guest and with which he developed a complex and often conflictual relationship."--
Keywords: Geschichte 1583; Heliozentrisches System; Philosophie; Italien; Copernicus, Nicolaus / 1473-1543; BODY, MIND & SPIRIT / Occultism; Astronomy / Early works to 1800; Occultism / Early works to 1900; Astronomy; Occultism; Early works; Quelle